The Purbaya Effect: Event Study of Leadership Signalling - Inta Hartaningtyas Rani; Lestari Adhi Widyowati; Jara Hardiyanti Jalih (Penerbit Goodwood, 2026)
Purpose: This study examines how the appointment of a new Minister of Finance affects stock price movements in the Indonesian capital market, with a focus on banking and manufacturing, which are directly affected sectors. Methodology/approach: This study uses an event-study design to investigate the existence of the “Purbaya Effect” by analyzing daily movements of the Jakarta Composite Index (JCI) and sectoral indices. Abnormal returns and cumulative abnormal returns are calculated using a 30-day window centered on the appointment date (September 8, 2025). Cross-sector sensitivity is assessed by comparing the short-term price responses of banking stocks, which are closely linked to fiscal-monetary transmission, and manufacturing stocks, which are more sensitive to demand expectations, the cost of capital, and risk sentiment. Results/Findings: The results confirm a significant “Purbaya Effect” at the aggregate market level following the ministerial appointment. Sectoral analysis indicates asymmetric responses: manufacturing stocks exhibit statistically significant price adjustments (sig 0.00<0.05), whereas the banking sector shows no comparable significant response (sig 0.183>0.05). Conclusions: Every cabinet change signals the quality of economic information to the capital market, which can be responded to negatively or positively Limitations: The study is confined to a 60-day event window, covers only two major sectors, and does not explicitly control for other macroeconomic or political events that may overlap with the announcement period. Contributions: The confirmation of the ‘Purbaya Effect” demonstrates that fiscal communication should be considered a signalling instrument with a real impact on price formation and capital allocation in the market.